CONSUMER LEGAL PROTECTION IN LAW NUMBER 30 OF 2000 CONCERNING TRADE SECRETS - Rahayu, Karlina (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
This article discusses legal protection efforts for consumers in Law Number 30 of 2000 concerning Trade Secrets, where there are still differences in understanding. The purpose of this writing is to find out how to understand trade secrets and how to protect consumer law therein, with a normative juridical approach, this research emphasizes library research methods. The rationale for this research departs from the enormous impact of Law Number 30 of 2000 concerning Trade Secrets on economic life. The research results show that the influence of Law Number 30 of 2000 concerning Trade Secrets has an impact on other regulations relating to the implementation and regulation of business in Indonesia. The existing Trade Secrets Law can no longer accommodate the current needs of society. This is due to the rapid development in society in general and business actors in particular as well as globalization which will inevitably affect people's lifestyles.